The Influence of Influencer Marketing, e-WoM, and Brand Image on The Purchase Intention of Viva Cosmetics Products on Tiktok Shop Consumers in Depok City - Fiddini Sharika Fawzi; Nur Fitri Dewi; Febria Anjara (Journal Research of Social Science, Economics, and Management, 2026)
The development of social commerce (s-commerce) through TikTok Shop encourages cosmetics companies to optimize digital marketing strategies to increase purchase intention. This study aims to analyze the influence of influencer marketing, electronic word of mouth (e-WOM), and brand image on the purchase intention of Viva Cosmetics products on TikTok Shop consumers in Depok City, both partially and simultaneously. This study uses an associative quantitative approach with a survey method of 110 respondents selected through purposive sampling techniques. Data were collected using questionnaires and analyzed by multiple linear regression using SPSS version 31. The results of the study show that influencer marketing, e-WOM, and brand image partially or simultaneously affect purchase intention. An Adjusted R² value of 0.677 indicates that all three variables are able to explain 67.7% of the variation in purchase intention. The results indicate that influencer-based marketing strategies, consumer reviews, and strong brand image contributes an important role in increasing purchase intention on TikTok Shop.